Accounting for Shear Anisotropy and Material Frame Rotation on the Constitutive Characterization of Automotive Alloys using Simple Shear Tests. (September 2020) - Abedini, A.; Noder, J.; Kohar, C.P.; Butcher, C.
Highlights: Simple shear tests remain free of plastic instability to large strains Simple shear data are converted to obtain hardening response to large strains Mechanics of shear deformation and anisotropy are considered for shear conversion Rotation of material axes is evaluated in shear conversion of anisotropic materials Developed normal stresses remain equal and opposite in simple shear Abstract: Simple shear tests are an increasingly attractive method to determine the equivalent stress-strain response of sheet metals. Unlike uniaxial tensile tests, shear tests can reveal the hardening behaviour of materials to large strains without stress state deviations triggered by tensile instability. However, there has been some uncertainty surrounding the interpretation of the shear response of anisotropic materials due to the definition of appropriate equivalent strain measures and the development of normal stresses. In the present study, the development of normal stresses during simple shear of anisotropic materials is analyzed and are found to be negligible relative to the magnitude of the applied shear stress. It is demonstrated that erroneous normal stresses may arise as a consequence of calibration of anisotropic yield functions. An experimental methodology was then proposed consisting of shear tests in multiple orientations to characterize shear anisotropy and account for rotation of the material frame on the hardening response. The methodology considers non-linear interpolation using either a calibrated yield function using both shear and tensile data or from a simplified phenomenological form calibrated using only the shear data. A range of automotive alloys were considered including DP980 and DP1180 advanced high strength steel alloys, an aluminum-magnesium alloy, AA5182-O, and an AA6063-T6 aluminum extrusion with severe anisotropy. It is demonstrated that for relatively isotropic materials such as the DP steels, accounting for material frame rotation results in an approximately 2% difference in the extracted hardening data compared to the case when the material rotation is neglected. This variation is expected to be within the experimental uncertainty. For materials with more pronounced anisotropy such as AA5182-O sheet and AA6063-T6 extrusions, the change in the hardening response is more significant and can reach up to 5% and 15%, respectively.